A baseline study of microplastic pollution in a Southern Indian Estuary. (January 2023) - Unnikrishnan, Vishnu; Valsan, Gokul; Amrutha, K.; Sebastian, Joju George; Rangel-Buitrago, Nelson; Khaleel, Rizwan; Chandran, Thara; Reshma, S.R.; Warrier, Anish Kumar
Abstract: Knowledge on the processes controlling the vertical distribution of microplastics (MPs) in estuaries is less. This research was carried out to determine the MP distribution in the surface, middle, and bottom layers of the Udyavara River Estuary in southwest India. The mean (± standard deviation) concentrations were 320.83 (± 98.30), 514.55 (± 352.16), and 755.03 (± 400.96) particles/m 3, respectively. Fibres, films, and fragments dominated, and 57 % of the MPs had a size range of 0.3–1 mm, while 43 % had a size of 1–5 mm. The main polymers were high-density polyethylene and polyethylene terephthalate. A positive correlation ( r = 0.421, p = 0.0205, n = 30) exists between the MPs and salinity, suggesting that the MPs are held by dense saline waters. The mean pollution load index value was 2.25 indicating severe pollution. Microplastic pollution is due to harbour, fishing, industrial activities, the effects of southwest monsoon rain, and tidal currents. Highlights: Vertical distribution of microplastics (MPs) in Udyavara River estuary Bottom water samples had the greatest MP abundance (mean: 755.03 particles/m 3 ). A large number of MPs belonged to the 0.3–1 mm size range. A positive correlation is evident between salinity and microplastic abundance. The mean pollution load index value of 2.25 indicates significant MP pollution.